Quality control in cervical cytology in the Cauca Department - Harold Jofré Bolaños-Bravo; Victoria Eljach-Pacheco; Sofía Freyre-Bernal (Revista de la Facultad de Ciencias de la Salud, 2010)
Introduction. This is descriptive work to show the findings of the internal and external quality control of the cervix uterus cytology in the Cauca's Department for the year 2009. Objective: Determine quality of the cytology of the cervix uterus in the Cauca Department. Methods: We worked with the gather information about the 9 laboratories and with the obtained results from the external quality control of the cervix uterus made by the Health's Laboratory public of the Cauca Health's Departmental Secretary. Results: We found that the cytology was made by not qualified or certificate personnel in most of the IPS and EPS that offer this service, the cytology's laboratories do not apply the recommendations of quality evaluation of the cervix uterus cytology,according to recommendations by Bethesda's system 2001. Conclusions: Is very important to continue and to strength the program of internal and external control of quality in cytology to guarantee the adequate functioning of the program and recover credibility in the cytology like the best method cost-effective in the cervix uterus cancer prevention.